2019
DOI: 10.35371/aoem.2019.31.e11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diabetes on 4-year changes of hearing thresholds in male workers exposed to noise in a single company: a longitudinal study

Abstract: BackgroundRecently, several studies have assessed the association between diabetes and hearing impairment. However, the effect of diabetes on hearing impairment is not well known in diabetic patients exposed to noise, a typical cause of hearing impairment. The aim of this study is to longitudinally analyze the effect of diabetes on hearing impairment in workers exposed to similar noise levels from 2013 to 2017 who had experienced little change in their working conditions.MethodsThe study subjects included 2,08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Meanwhile, Yadav and Yadav, 2018 in their study on Indian workers found that only for mixed bilateral hearing loss, NIHL analysis by audiometry revealed significant differences between diabetic and non-diabetic groups. Another study conducted by Kim et al 2019, which analyze the effect of diabetes on hearing impairment in workers exposed to similar noise levels from 2013 to 2017. The study subjects included 2,087 male workers exposed to noise in a single company, who underwent health examinations at the same hospital in Ulsan city, Korea .They found that the average PTA thresholds and their average changes between 2013 and 2017 were significantly higher in the diabetes mellitus (DM) group compared to the normal and impaired fasting glucose group.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Yadav and Yadav, 2018 in their study on Indian workers found that only for mixed bilateral hearing loss, NIHL analysis by audiometry revealed significant differences between diabetic and non-diabetic groups. Another study conducted by Kim et al 2019, which analyze the effect of diabetes on hearing impairment in workers exposed to similar noise levels from 2013 to 2017. The study subjects included 2,087 male workers exposed to noise in a single company, who underwent health examinations at the same hospital in Ulsan city, Korea .They found that the average PTA thresholds and their average changes between 2013 and 2017 were significantly higher in the diabetes mellitus (DM) group compared to the normal and impaired fasting glucose group.…”
Section: Discussionmentioning
confidence: 99%